Teori Nativisme, Empirisme, Konvergensi dan Fitrah: Analisis Perbandingan - Radjaming, Nawir (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Educational science has suggested that there are two factors that influence human development, namely: potential (innate) factors and environmental factors. Education does not have the slightest influence and does not play a role in the formation and development of a person's potential. The stages of preparing articles using library research include preparing relevant literature with titles based on books and related scientific journals. Arrange words related to the article and finally prepare a bibliography that is appropriate to the content of the article. The data sources used as reference material in writing articles are in accordance with the applicable template in the form of books, journals and internet sites related to the selected topic. 60% of the reference material in the preparation comes from scientific articles from scientific research journals and 40% comes from books related to the title of this article. Nativism is a school of education that understands that humans have potential within themselves that cannot be influenced by environmental factors. Empiricism is a school of education that understands that humans initially have potential within themselves but what determines it is environmental (external) factors. The Convergence School is a school that tries to combine the flow of nativism and empiricism on the pretext that humans are equipped with potential but to develop it better there needs to be demand and guidance through education. Fitrah is the basic potential that exists within humans, while humans have good and bad tendencies, so it is fitra that needs to be sharpened through education to create pious Muslims